Student partnership in creating an event: Benefits, challenges, and outcomes - Kitchen, Eliza (International Journal for Students as Partners, 2023)
This case study explores a partnership within an events management topic. Students were encouraged to take ownership over the creation and operation of an event held on the university campus. The topic lecturer provided guidance throughout the process and liaised with the students to define the assessment and the marking rubric for the event project. Research data was captured through two surveys—one during the event project and one after the event project was completed. The surveys captured quantitative and qualitative data about students’ perceptions on the benefits, challenges, and outcomes of this experiential learning experience. Survey findings indicated that communication and teamwork were key aspects that needed to be managed to effectively collaborate on the project. Classroom discussion and online communication tools were used to share ideas and information, and work towards the common goals of the event. Through this project, students developed their relationships with their peers and university staff and felt that they had a valuable learning experience that helped to connect theory with practice.